A Two-year Longitudinal Study of Dental Caries in Permanent First Molars of Korean Elementary Schoolchildren - Bon-Kyoung Cho, DDS, MPH; Ho-Keun Kwon, DDS, PhD; Kwon-Soo Kim, DDS, MPH; (Blackwell Synergy, 2001)
This longitudinal study investigated dental caries increment in permanent first molars of Korean elementary schoolchildren. Methods: A convenience sample of 722 children aged 7-9 years attending one urban elementary school was examined at baseline, with follow-up examinations at one and two years. Coronal surfaces of permanent first molars were scored with regard to caries experience and sealant status.